Analysis of content development in chemical materials related to ethnoscience: a review - Widarti, Hayuni Retno; Wiyarsi, Antuni; Yamtinah, Sri; Siddiq, Ari Syahidul; Sari, Meyga Evi Ferama; Fauziah, Putri Nanda; Rokhim, Deni Ainur (Journal of Education and Learning (EduLearn), 2025)
One way to preserve culture in education is through ethnoscience-based learning, especially in chemical materials linked to various fields of science in life, including social and cultural. Ethnoscience is a process of reconstructing indigenous science knowledge with scientific science. This research aims to explore trends in ethnoscience-based chemistry learning in Indonesia and analyze the contents, focusing on topics, learning approaches and models, tools, and variables influenced. The research data collection method adopted the preferred items for systematic review and meta-analysis (PRISMA) design and obtained from 30 selected articles indicated from 2019-2024 published in journals indexed by Scopus and SINTA. Analysis results show that the process of making batik is one of the ethnoscience topics that are widely used in chemistry learning. Ethnoscience learning can also be done by combining local wisdom (culture), traditional foods, and natural phenomena of the environment. Ethnoscience learning can be integrated into various learning models, such as contextual teaching and learning (CTL), problem-based, and project-based learning (PjBL). Learning tools often used in ethnoscience-based chemistry learning are modules, evaluation instruments, and worksheets. Ethnoscience is interesting to learn because it positively affects critical thinking and creativity, cultural and conservation character, and scientific literacy.